MONITORING HAMA DAN PENYAKIT TANAMAN DALAM PERLINDUNGAN KOLEKSI TANAMAN DI KEBUN RAYA PURWODADI - Linda Wige Ningrum; Dewi Retnosari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Purwodadi Botanical Garden is a botanical garden that specifically designated to ex situ plant conservation with typical habitats of low lands and dry areas. In an effort to protect and maintain the collection of plants, one of the things that must be carried out is the monitoring of plant pests and diseases. The research aimed to find out the plant pests and diseases that infect in plant collections at Vak I-V in Purwodadi Botanical Gardens. The method used was a descriptive observation and literature study, while the secondary data were books and environmental maps. There were nine types of pests and nine types of diseases. Pests and diseases are dominated by Leaf Spot Disease, Black Ants, Red Ants, and Lawana candida. They attack some plants, such as from family of Sapotaceae, Sterculiaceae, Mimosaceae, Moraceae, etc. The results of this study can be used as a material consideration in efforts to prevent and increase ex-situ conservation in the Purwodadi Botanical Garden.